Effect of oil rich in monounsaturated fatty acid and polyunsaturated fatty acids on lipid profile and glucose level in male Wistar rats - Dina M Trabzuni (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2020)
Dietary fats and oils are responsible for concentrated source of energy for human metabolic processes. This study was carried out to determine the effects soybean (SOBO), olive (OLVO) and hazelnut (HAZO) on lipid profile and glucose level in male Wistar rats. Fifteen male Wistar rats weighting between 150-170 grams were divided randomly into three groups of five rats each. Groups 1 (Control group, SOBO) was assigned to receive 30 grams of the control diet with soybean oil per day. Group 2 was allocated to take 30 grams of the diet with olive oil per day and group 3 was allocated to receive 30 grams of the diet with hazelnut oil per day. Initial weight of rats was highest in soybean group followed by olive and hazelnut oil (SOBO > OLVO > HAZO). Similar trend was observed in final weight, weight gain and growth rate of rats (SOBO > OLVO > HAZO). Statistically insignificant difference was observed between control (SOBO group) and experiments groups (OLVO and HAZO) for all growth parameters. Least value of TC was observed in olive group but the difference was insignificant between the groups. Similarly the difference for TG, LDL-C, VLDL-C and glucose was also statistically insignificant the groups. Only for HDL-C the difference between the groups found was statistically significant. To summarize, in this study; different MUFA and PUFA rich oil did not significantly altered lipid profile of male Wistar rats.  It also didn’t exhibit any major effect on weight. Only for HDL-C the difference between the groups found was statistically significant.